Effects of HDPE Utilization and Addition of Wetfix-Be to Asphalt Pavement in Tropical Climates - Daud Nawir; Achmad Zultan Mansur (Salehan Institute of Higher Education, 2022)
Plastic Waste (PW) is one of the primary sources of pollution, leading to drainage system blockages, thereby causing floods and road pavement damage. One of the major ways to reduce pollution due to plastic waste and excessive exploitation of natural resources is through the development of HDPE. It is also important to reduce damage to road pavement structures by improving the quality of the asphalt used during construction. Therefore, this research aims to analyze the effects of using HDPE shale, an ecologically friendly material, and the addition of Wetfix-Be to asphalt pavements in tropical climates. The study results showed that 5.75% of the OAC asphalt using plastic waste raises the stability value and meets the specification requirements. Specimens of AC-WC concrete asphalt mixture were also tested by immersing them in fresh and seawater for 0.5, 24, 72, and 96 hours. In conclusion, using HDPE plastic waste and Wetfix-Be keeps the AC-WC concrete asphalt mixture stable. Doi: 10.28991/CEJ-2022-08-08-010 Full Text: PDF